2002
DOI: 10.1023/a:1014379127240
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid anxiety disorders in civilians seeking treatment for posttraumatic stress disorder

Abstract: Research indicates that posttraumatic stress disorder (PTSD) is associated with high rates of comorbid psychiatric diagnoses. Yet, it remains unknown whether PTSD is associated with greater comorbidity relative to patients with other anxiety disorders. This study examined prevalence of comorbid anxiety disorders with PTSD relative to other disorders among a treatment-seeking population. Patients with PTSD (n = 83) evidenced greater overall comorbidity as compared to patients with other anxiety (n = 151) or Axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…In the National Comorbidity Survey, Kessler et al [1995] determined that the comorbidity rate for PD and PTSD in a large, nationally-representative community sample was 7.3% (SE¼2.3) for males and 12.6% (SE¼2.3) for females. The rates of PTSD/PD comorbidity range from 8-18% in studies examining clinical samples [McFarlane and Papay, 1992;Zayfert et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…In the National Comorbidity Survey, Kessler et al [1995] determined that the comorbidity rate for PD and PTSD in a large, nationally-representative community sample was 7.3% (SE¼2.3) for males and 12.6% (SE¼2.3) for females. The rates of PTSD/PD comorbidity range from 8-18% in studies examining clinical samples [McFarlane and Papay, 1992;Zayfert et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Those with PTSD often have comorbid diagnoses of major depressive disorder, dysthymia, general anxiety disorder, or social phobia (Schnurr & Friedman, 1997;Zayfert, Becker, Unger, & Shearer, 2002). In addition, PTSD is associated with a variety of risky health behaviors including alcohol and other substance use and abuse, poor diet, and lack of exercise and preventative health care (Schnurr & Friedman, 1997;Rheingold, Acierno, & Resnick, 2004;Pederson, Van Horn, Wilson, Martorano, Venema, & Kennedy, 2008).…”
mentioning
confidence: 99%
“…Accordingly, a number of previous studies have found high rates of severe psychological trauma (88% in the study of Bandelow and coworkers [34]) or even PTSD (15% in the study by Goisman et al [38]) among patients with SAD, as well as an increased prevalence of SAD among patients with PTSD (ranging from 43 [39,40] to 74% [41]). …”
Section: Discussionmentioning
confidence: 93%